STRUCTURED HABIT TRAINING AND GUIDANCE COUNSELING SUPPORT FOR EARLY CHILDHOOD CHARACTER DEVELOPMENT - Zahra Ainul Inayah; Nenda (EDUCATIONE, 2026)
Character education in early childhood settings is increasingly expected to be systematic and sustainable; however, schools often vary in how consistently they implement habit training and in how actively guidance and counseling services support character formation. This study aimed to compare the implementation of habit training in a general school and a character-based school, and to analyze the role of guidance and counseling (BK) in strengthening children’s character development. Using a qualitative comparative design, data were collected through classroom and school observations, in-depth interviews with principals, teachers, counselors, and parents, and document analysis of habituation programs in two institutions (TK-TPQ Nurkatika as a general school; KB-TK Pilar Aksara as a character-based school). The findings indicate substantial differences between the two settings: the character-based school implemented integrated and consistent habituation routines supported by regular parent communication, modeling, periodic evaluation, and parenting activities, whereas the general school tended to apply habituation in a more generic manner without a structured program and with less optimal BK involvement. Consequently, children in the character-based school demonstrated more stable positive behavior that also carried over into the home environment. The study concludes that structured habit training aligned with targeted BK services meaningfully enhances the effectiveness of character building. Practically, schools may benefit from formalizing habituation programs, strengthening counselor participation, and institutionalizing school–home collaboration. Future research should involve broader samples, incorporate longitudinal or mixed-method designs, and examine implementation constraints that may affect comparability across schools.